The Influences on Direct Communication in British and Danish Firms: Country, 'Strategic HRM' or Unionization? - Croucher, R; Gooderham, P; Parry, Emma (Sage Publications, 2006)
This paper examines the antecedents of private sector managers’ propensity to communicate directly to employees in Britain and Denmark by use of largescale survey data. It tests Brewster’s (1995) argument that European HR managers are constrained in applying American versions of HRM and considers other theories suggesting that companies in the two countries would have different drivers of their communications practices. It is also relevant to ‘varieties of capitalism’ discussions of how national systems structure firm-level behaviours. It finds two antecedents for managers’ propensity to communicate directly, irrespective of country: whether the senior HR manager is involved in 3 strategy formation and the degree of unionisation. These are common to companies operating in both Britain and Denmark and it is therefore concluded that Brewster’s argument must to that extent